PENEGAKAN HUKUM TERHADAP LARANGAN NOTARIS BEKERJASAMA DENGAN BIRO JASA DALAM KAITANNYA DENGAN KODE ETIK NOTARIS - , CITRA INDRIA PUTRI; , Sigid Riyanto, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to identify and analyze law enforcement against prohibition notaries who work with service bureaus and constraints faced by the MPD and DKD Palembang in carrying out enforcement against prohibition notaries who work with service bureaus. This study is an empirical study, in which the data used in this study is primary data and secondary data. Primary data is data obtained through interviews with respondents. While secondary data is data obtained from the literature to obtain legal materials that are primary and secondary. Sampling techniques in non-random sampling with the type of sampling is purposive sampling, the data were analyzed qualitatively and subsequently presented descriptively. The results showed that the notary law enforcement against prohibition by working with service bureaus and DKD Palembang MPD has not been done. This is because the MPD has not been exercising its authority as referred to in Article 70 a and DKD UUJN not carry out an examination of the mechanisms of notary as defined in Article 9 of the Code notary so that the absence of sanctions imposed by the MPD and DKD as referred to in Article 6 of the Code Notary. Constraints faced by the MPD and DKD Palembang in carrying out enforcement against prohibition notaries who work with service bureaus by 5 (five) factors that affect law enforcement, namely: 1) the same powers between MPD and DKD to hold a hearing on alleged violation of code of conduct by the notary